The impact of major public health emergencies on Trust in Government: From SARS to COVID-19 - Zhai, Kun; Yuan, Xuemei; Zhao, Guoqing (Frontiers in Psychology, 2022)
Major public health emergencies always test the credibility of the government. The success of governments’ strategies relies on trust in government and broad acceptance of response measures. The profound experience of the epidemic often has a long-term impact on people’s cognition. We construct a difference-in-difference estimator by combining the variations of epidemic effects across cohorts and regions and intend to evaluate the long-term effect of individuals’ early SARS experience on trust in government during the COVID-19 pandemic. We also use the instrumental variable method to overcome the endogenous problem caused by two-way causality. The results show that the impact of COVID-19 has significantly reduced trust in government of the groups who had not been exposed to the SARS epidemic (including groups who were in early childhood and the unborn during the SARS outbreak). While it has a positive impact on trust in government of people experienced SARS in adolescence, and only a little negative impact on trust in government of people experienced SARS in adulthood. We also find that the impact of COVID-19 mainly reduced the trust in government among groups socially vulnerable or without SARS experience (e.g., low income, low social status etc.). The results suggest that: (a) the trust created by governments’ successful anti-epidemic measures is long-lasting; (b) governments should pay more attention to their trust among socially vulnerable groups.